Pengaruh Struktur Modal Terhadap Pajak Penghasilan Badan Terutang Pada Perusahaan Sektor Industri Barang Konsumsi Di Bursa Efek Indonesia - Tia Novira Sucipto; Renika Hasibuan (Jurnal Riset AKuntansi dan Bisnis, 2020)
This study aims to determine the effect of longterm debt to asset ratio and debt to equity ratio on corporate income tax payable in Consumer Goods Industry Sector Companies in the Indonesia Stock Exchange 2014-2018 period. The research method used is descriptive quantitative because the data used is in the form of numbers. The population in this study is the Consumer Goods Industry Sector Companies in the Indonesia Stock Exchange for the 2014-2018 period. The number of samples used in this study were 14 companies. The coefficient of determination (R square) is 0176 or 17.6%. This means that the independent variables, namely the long-term debt to asset ratio (LDAR) and the debt to equity ratio (DER), explain their effect on the dependent variable, namely corporate income tax payable to the Consumer Goods Industry Sector companies on the Indonesia Stock Exchange for the 2014-2018 period of 17, 6% while the remaining 82.4% is explained by other variables that are not explained in this research model.